Marginal Discrepancy and Fracture Resistance of CAD/CAM Ceramill Sintron Metal Copings with Different Porcelain Materials - Al-Saady, Ammar A; Abdulghani, Mustafa N; Jellil, Eanas I (Journal of Baghdad College of Dentistry, 2017)
Background: This study was performed to compare the marginal fit changes and facture resistance of metal ceramic crowns constructed from Ceramill Sintron metal coping veneered with three different porcelain veneering materials (Vita Master Koromikos VMK, Willi Geller Creation CC and GC initial MC), also to evaluate the influence of thermocycling on load at fracture. Materials and Methods: Master brass die was scanned ,then metal coping was designed and milled from Ceramill Sintron blank to get 60 metal copings, then divided randomly into three groups(20 sample), then veneered with porcelain: VITA, Creation or GC. The marginal gaps were measured before and after porcelain veneering then marginal fit changes was calculated. Fracture resistance test was done by InstronÂ®, the master die was duplicated to sixty analogs then each analog was fixed into acrylic base. After that each crown was cemented onto the corresponding die analog. Ten samples of each group were subjected to compressive loading to fracture and other ten subjected to thermocycling followed by compressive loading to fracture. Result and Conclusion: The result of marginal fit changes showed that GC group had the lowest marginal gap follow by VITA and Creation. While VITA group showed the highest fracture resistance follows by GC then Creation. Thermocycling process did not significantly reduce the load at fracture for all groups.